Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1159/000111798
|View full text |Cite
|
Sign up to set email alerts
|

Voice Range Profiles for Tonal Dialect of Min

Abstract: The influence of frequency and intensity in Min dialect on maximum vocal performance has not been investigated. The purposes of this study are (1) to investigate the physiological frequency and intensity ranges of the tonal dialect of Min, and (2) to compare the physiological frequency and intensity ranges of Min to those of nontonal languages. The subjects were 40 normal Taiwanese adults. All subjects were native Min speakers. The lowest frequency, the highest frequency, the maximum range of vowel frequency c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 52 publications
(68 reference statements)
0
17
1
Order By: Relevance
“…Nora Siupsinskiene and Hugo Lycke Voice Training and Vocal Capabilities e185 separate norms for male and female subjects were established. 1,3,8,19,[30][31][32][33][34]47 Our analysis of vocally healthy trained adult choir singers and adult nonsingers showed that singers demonstrated increased vocal capabilities, especially measured by VRP. Both male and female singers when compared with nonsingers demonstrated significantly increased mean pitch range, higher highest frequency, and increased VRP area in high frequencies (P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nora Siupsinskiene and Hugo Lycke Voice Training and Vocal Capabilities e185 separate norms for male and female subjects were established. 1,3,8,19,[30][31][32][33][34]47 Our analysis of vocally healthy trained adult choir singers and adult nonsingers showed that singers demonstrated increased vocal capabilities, especially measured by VRP. Both male and female singers when compared with nonsingers demonstrated significantly increased mean pitch range, higher highest frequency, and increased VRP area in high frequencies (P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…1,19,23,[26][27][28][29][30][31][32] The VRP is known to be sensitive to gender and age, consequently separate norms for male and female subjects and children are reasonable. 3,9,14,[22][23][24][25][30][31][32][33][34][35] Although the significant differences between prepubescent child and adult voices are well established, only limited data on normal vocal capabilities for trained voices in school-aged children is available. 8,[20][21][22] This may be because of some difficulties in the testing of children (more time consuming, less precise) and of variability of the data as a result of rapid and obvious changes in the anatomy and physiology of the vocal tract during development.…”
Section: Introductionmentioning
confidence: 99%
“…For example, tonal Chinese speakers had greater physiological frequency range and physiological dynamic intensity range than non-tonal language speakers. 7,8 The study suggested that daily conversation in Chinese may…”
mentioning
confidence: 99%
“…For example, tonal Chinese speakers had greater physiological frequency range and physiological dynamic intensity range than non-tonal language speakers. 7,8 The study suggested that daily conversation in Chinese may enhance respiratory and laryngeal muscle strength, endurance and flexibility, leading to an increased maximum vocal performance, as indicated by frequency and intensity. 8 However, these data were all obtained from normal-hearing people.…”
mentioning
confidence: 99%
See 1 more Smart Citation